An efficient method for increasing the accuracy of mobility maps for ground vehicles. (December 2016) - Gonzalez, Ramon; Jayakumar, Paramsothy; Iagnemma, Karl
Highlights: Methodology for the interpolation of a DEM to a finer resolution. Segmentation-based approach where stationarity is ensured. Fractal dimension and elevation range metrics for determining local variograms. Empirical validation based on natural and man-made terrains. Abstract: This paper presents an efficient method for increasing the accuracy of one key step regarding the process of determining a mobility map. That is, the interpolation of the original Digital Elevation Model (DEM) to a finer resolution before running multi-body-dynamics simulations. Specifically, this paper explores the use of fractal dimension and elevation range metrics for increasing the accuracy and reducing the computation time associated with the spatial interpolation ordinary kriging method. The first goal is to ensure the stationary variogram requirement. The second goal is to reduce kriging error or variance in the new predicted values. A novel segmentation-based approach has been proposed to divide the regions of interest into segments where stationarity is ensured. Empirical investigation based on real DEMs indicates the generality of the segmentation approach when natural and man-made terrains are considered. The proposed method leads to a more efficient computation burden and to more accurate results than the traditional approach.